THE ROLE OF INCLUSIVE EDUCATION IN REDUCING LEARNING DISPARITIES AMONG STUDENTS FROM DIFFERENT ECONOMIC BACKGROUNDS - Fitriyanti Fitriyanti; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the role of inclusive education in reducing learning gaps between students from different economic backgrounds using a literature review method. A systematic review of various sources, such as books, scientific journals, articles, and relevant policy documents, was conducted to gain a comprehensive understanding of the practices, challenges, and strategies of inclusive education in various contexts. The results of the literature study indicate that inclusive education contributes to expanding access to quality education for all students, especially economically disadvantaged groups, through adaptive policies such as fee subsidies, exemption from infaq (voluntary donations), and the use of affordable educational technology. However, its effectiveness is still influenced by factors such as limited teacher competence, uneven infrastructure, and social and cultural resistance in the school environment. Thus, inclusive education supported by progressive policies, continuous teacher training, and multi-stakeholder collaboration can be an effective strategy to narrow learning gaps and promote educational equity